Viewing the Development of Tulungagung Artistry - Widodo, Triyono; Indrawati, Lilik; Ponimin, Ponimin; Dhesti Anggriani, Swastika (KnE Social Sciences, 2023)
The existence and development of art in a region of Indonesia is perceived as a form of support and contribution to the existence of art in Indonesia, while it can also be part of the capital strength and dignity of a nation. The same goes for the efforts to trail the development of art in Tulungagung as a part of modern art in East Java. It is the gait and character of the driving artists that voice and move the next generation of modern art, so that Moelyono’s role as a character in the Tulungagung arts can drive the next young generation in both Tulungagung and East Java. This condition encourages our research to see the modern art in Tulungagung. This research leverages the qualitative approach by filtering the data through document analysis and interviews. The result of classification and data analysis describes that modern art in Tulungagung, based on the periodization model by Sanento Yuliman, can be recorded in the third period (1960-present). Although there were no traces of the first period (Mooi Indie 1900-1940) and the second period (1940-1960), the development of Tulungagung art in the third period also seems to be dominated by the figures of college graduate artists from Art College in Indonesia. Therefore, the classification of the periodization of art development in Tulungagung is named by: (1) the period of Art College influence in Indonesia 1970-1980s, (2) the period of Art College influence in Indonesia 1980-1990s, (3) The Period of Art College influence in Indonesia 1990-2000s. Keywords: art development, modern art, artist